Teaching disaster risk management: lessons from the Rotman School of Management (2016)
This article describes how disaster risk management topics are taught at the Rotman School of Management at the University of Toronto and thus highlights opportunities for developing similar course modules on disaster risk management at other institutions. An undergraduate and MBA elective course, titled Catastrophic Failure in Organizations, contains four modules that are directly relevant to disaster risk management. The first module focuses on the need to move from risk indifference to risk sensitivity. The second module considers the importance of business continuity and crisis management plans and explores their common shortcomings. The third module uses a case study to examine the topic of prospective risk management. The fourth module focuses on the vulnerability of supply chains and other complex systems to disaster risk. The article describes the details of implementing these modules and discusses opportunities for further integration of disaster risk management topics in other parts of the curriculum